Exactly separable version of the Bohr Hamiltonian with the Davidson potential - Bonatsos, D.; McCutchan, E. A.; Minkov, N.; Casten, R. F.; Yotov, P.; Lenis, D.; Petrellis, D.; Yiyitoglu, I. (HNPS Advances in Nuclear Physics, 2020)
An exactly separable version of the Bohr Hamiltonian, is obtained by using a potential of the form V (β, γ) = u(β) + u(γ)/β2, with a Davidson potential for u(β) and a stiff harmonic oscillator potential centered around γ = 0o, for u(γ). Using two parameters (β0 and the γ-stiffness parameter) the band features and B(E2) transition rates of almost all well-deformed rare-earth and actinide nuclei are reproduced, while the spectrum of the SU(3) dynamical symmetry of the Interacting Boson Model can be obtained, for the first time using the Bohr Hamiltonian.